ANALISIS KANDUNGAN FORMALIN PADA IKAN SEGAR DI PASAR TRADISIONAL KOTA SERANG - Siti Komariah Maulia; Yulda Yulda; Agung Setyo Sasongko (JURNAL PERIKANAN TROPIS, 2026)
Fish is an important food for their essential nutrients and has numerous health benefits. However, fishery products are highly perishable and prone to rapid quality deterioration. Although the use of formalin as a food preservative is prohibited, it is still frequently detected in fishery products. This study aims to determine formalin levels and evaluate the organoleptic characteristics of various fresh fish species sold at traditional markets in Serang City. The study used observational methods with purposive sampling. Formalin content was analyzed qualitatively, while organoleptic characteristics were assessed using hedonic testing based on appearance, gills, mucus, flesh, odor, and texture. The results showed that 3 out of 10 fish species tested positive for formalin: Milkfish, Tilapia, and Flounder fish. For Tilapia, the average scores were 6.99 (positive) and 6.48 (negative). For Flounder fish, the scores were 6.69 (positive) and 7.05 (negative). According to the Indonesian National Standard, the average organoleptic scores of milkfish (both positive and negative) and negative formalin flounder fell into the “Fresh Fish” category. Overall, there was only a slight difference in organoleptic scores between fish containing formalin and those without, making them difficult to distinguish by sensory evaluation alone.Keywords: fishery product, flounder fish, organoleptic, perishable, qualitative